School Safety and Security Types in Indonesian Rural and Urban Early Childhood Education Units - M. Agung Hidayatulloh; Muhamad Rozikan; Arina Musta'anah (SEA-CECCEP, 2022)
A number of cases are known to threaten the safety and security of early childhood in Indonesia. There are incidents that result in children being injured, almost kidnapped, and even causing the child to die. This study seeks to capture what types of safety and security implemented in four early childhood education (ECE) units in Indonesia. This type of research is descriptive qualitative. This study used interview, observation, and documentation for data collection. Semitructured interviews were used to obtain data from kindergarten teachers and principals, and parents. Observation was used to observe a number of activities in kindergarten that reflect the implementation of school safety and security. The documentation technique was used to identify a number of documents related to the topic of study. Among the documents collected here were regulations/laws, photographs, SOP, and written documents of ECE units (semester program, weekly and daily lesson plans), and facilities related to school safety and security. The data analysis process of this research included data reduction, data display, and conclusion drawing. The results show that both physical and psychosocial safety and security have been attempted in the four ECE units. Physical safety and security, among others, is represented by providing insight to children about how to go up and down stairs. In ECE units that are prone to disasters, they are taught how to protect themselves when a volcano erupts and how to safely deal with floods. Psychosocial safety and security is demonstrated by the values and attitudes that are upheld by teachers and education personnel in ECE units. Those values and attitudes include inclusiveness, caring, smiling, sociable, responsive, sharing, polite, and trusting each other. Of these values, it is recognized that inclusiveness still requires a lot of stimulation, both on the teacher and child side. This finding implies that the two types of safety and security need to be maintained and improved.